KETERLEKATAN INTERNET DALAM AKTIVITAS KESEHARIAN DAN PENDIDIKAN GENERASI MILENIAL - Rizki Setiawan (Fakultas Seni Rupa dan Desain ITB, 2021)
This article aims to explore the embeddedness both the millennial generation to the internet in daily activities and education at the local level. This research uses concurrent mixed methods with a survey and interview strategy simultaneously. The results showed the uniqueness of the Banten millennial generation’s engagement with the internet as follows: (i) informants learned to use the internet more by themselves; (ii) they use internet more for social media; (iii) they still like shopping and use conventional modes of transportation; (iv) most of them cannot carry out their daily activities without the internet; (v) daily activities are undertaken without an agenda but have a specific target. Furthermore, in the interaction between technology and education, it is found: (i) technology is related to information seeking for the millennial generation; (ii) they prefer to find information through browsing; (iii) only a small proportion of them have experimental learning attitudes; (iv) the majority of the millennial generation views that the existence of teachers is still the main factor in learning.